Myocardial repair of bioengineered cardiac patches with decellularized placental scaffold and human-induced pluripotent stem cells in a rat model of myocardial infarction - Jiang, Yu (Stem Cell Res Ther, 2021)
BACKGROUND: The creation of a bioengineered cardiac patch (BCP) is a potential novel strategy for myocardial repair. Nevertheless, the ideal scaffold for BCP is unknown. OBJECTIVE: We investigated whether the decellularized placenta (DP) could serve as natural scaffold material to create a BCP for myocardial repair. METHODS AND RESULTS: A BCP was created by seeding human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs; 1 × 106/cm2) onto DP. The functional and electrophysiological properties of the BCP were first characterized by in vitro analysis and optical mapping. Next, in vivo therapeutic efficacy of the BCP was evaluated in a rat model of myocardial infarction (MI), created by left descending coronary artery ligation (MI + BCP group), and compared with MI alone (MI group), transplantation of DP (MI + DP group), and hiPSC-CMs (MI + CM group). Cytokine profiling demonstrated that the BCP contained multiple growth and angiogenic factors, including vascular endothelial growth factor, platelet-derived growth factor, insulin-like growth factor-1, basic fibroblast growth factor, angiogenin, and angiopoietin-2. In vitro optical mapping showed that the BCP exhibited organized mechanical contraction and synchronized electrical propagation. RNA sequencing showed that DP enhanced the maturation of hiPSC-CMs compared with the monolayer of cultured hiPSC-CMs. At 4 weeks follow-up, the BCP significantly improved left ventricular (LV) function, as determined by LV ejection fraction, fractional shortening, + dP/dt(max), and end-systolic pressure-volume relationship, compared with the MI, MI + DP, and MI + CM groups. Moreover, histological examination revealed that engraftment of the BCP at the infarct zone decreased infarct size and increased cell retention and neovascularization compared with the MI, MI + DP, and MI + CM groups. CONCLUSIONS: Our results demonstrate that a DP scaffold contains multiple growth and angiogenic factors that enhance the maturation and survival of seeded hiPSC-CMs. Transplantation of a BCP is superior to DP or hiPSC-CMs alone in reducing infarct size and improving cell retention and neovascularization, thus providing a novel therapy for myocardial repair following MI. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13287-020-02066-y.